KALIGRAFI TENTANG ANJURAN SHOLAT BERJAMAAH DALAM KARYA SERIGRAPHY - M. IRSYAD, Yofita Sandra, S.Pd., M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2019)
This final work visualizes the prayer recommendations in congregation in order to shape social behavior in the lives of oneself and society, through graphic print design (serigraphy). The method and process of the works used in the creation of works, through several stages: (1) preparation, (2) elaboration, (3) synthesis, (4) realization of concepts (5) finising. The result of the discussion is a visualization of prayer in congregation. The works produced are: Middle, Bowing, Obedient, First Syaf, Adhan, 27 degrees, Mastered by Shaytan, Other Groups, Comparison, and Consistent. These are the main points that can shape social behavior in social life and morals.Kata Kunci : Sholat Berjamaah, Kaligrafi, Seni Grafis, Serigraphy